2016
DOI: 10.1021/acs.biochem.5b01059
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N-Terminal Extension of Cardiac Troponin I on the Ca2+ Regulation of ATP Binding and ADP Dissociation of Myosin II in Native Cardiac Myofibrils

Abstract: Cardiac troponin I (cTnI) has a unique N-terminal extension that plays a role in modifying the calcium regulation of cardiac muscle contraction. Restrictive cleavage of the N-terminal extension of cTnI occurs under stress conditions as a physiological adaptation. Recent studies have shown that in comparison with controls, transgenic mouse cardiac myofibrils containing cTnI lacking the N-terminal extension (cTnI-ND) had lower sensitivity to calcium activation of ATPase, resulting in enhanced ventricular relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 82 publications
1
12
0
Order By: Relevance
“…Skeletal myofibrils were isolated from mouse gastrocnemius muscle. 66 Initially the frozen muscle was thawed on ice and cut into small pieces, followed by homogenization in a cold lysis buffer (10 mM Tris-HCl, pH 7.0, 5 mM EGTA, 130 mM NaCl, 5 mM KCl, 1 mM MgCl 2 , 1 mM NaN 3 , 1 mM DTT, 0.1 mM PMSF, 10 μM E-64, 100 μM leupeptin and protease inhibitor cleavage cocktail) using an electronic homogenizer. Homogenates were then pelleted at 4 °C by centrifugation for 5 min at 2,500 x g .…”
Section: Methodsmentioning
confidence: 99%
“…Skeletal myofibrils were isolated from mouse gastrocnemius muscle. 66 Initially the frozen muscle was thawed on ice and cut into small pieces, followed by homogenization in a cold lysis buffer (10 mM Tris-HCl, pH 7.0, 5 mM EGTA, 130 mM NaCl, 5 mM KCl, 1 mM MgCl 2 , 1 mM NaN 3 , 1 mM DTT, 0.1 mM PMSF, 10 μM E-64, 100 μM leupeptin and protease inhibitor cleavage cocktail) using an electronic homogenizer. Homogenates were then pelleted at 4 °C by centrifugation for 5 min at 2,500 x g .…”
Section: Methodsmentioning
confidence: 99%
“…The differences would also be due to the length of the synthetic peptides that were used instead of a full-length cTnI we used. In fact, there was no measurable increase in the calcium affinity of cTnC upon peptide-cTnC complex formation 16 , although the full-length cTnI increases the affinity markedly 912 .…”
Section: Resultsmentioning
confidence: 95%
“…The changes in the quantum yield of the fluorescence label at the residue of the N-extension of cTnI showed that it complexed with cTnC even at 0.3 M KCl 18 . Additionally, the N-extension-dependent regulation of the calcium binding affinity occurs in the actomyosin complex 9,12 or in muscle fiber 10,11 at physiological ionic strength. Upon binding their target protein, however, IDRs were assumed to lose most of their conformational freedom and adopt a well-defined structure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This extension is functional for sufficient opening of the cTnC N-domain [75][76][77], as well as maintaining the normal Ca 2+ sensitivity of cTnC [61,[78][79][80]. Furthermore, two phosphorylation sites (amino acid residue numbers Ser23, Ser24 and Ser42, Ser44) for protein kinase A (PKA) and C (PKC), respectively, are present in or adjacent to this extension and modulate Ca 2+ sensitivity after phosphorylation [81,82]. The structure and location of the N-terminal extension were studied by NMR, X-ray/neutron scattering, FRET, and PELDOR/DEER, but little is known because of its intrinsically disordered protein (IDP) nature [65,[83][84][85][86].…”
Section: Regulation Of Myosin Atpase By the Actin-troponin-tropomyosimentioning
confidence: 99%